Strategi Pendidikan Pesantren Al-Mujahidin Samarinda dalam Menangkal Paham Radikalisme di Lingkungan Santri - Salim, Muhammad; Durase, M. Abzar; Khojir, Khojir (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2024)
Religious radicalism remains a significant challenge for Islamic education institutions, including pesantren (Islamic boarding schools). This study explores the de-radicalization strategies employed by Pesantren Al-Mujahidin in Samarinda to prevent radical ideologies among santri (students). A qualitative approach with a case study design was adopted. Data were collected through in-depth interviews, participatory observation, and document analysis, and were subsequently analyzed thematically. The findings reveal three key strategies: (1) the internalization of national values through the Tausiah Kebangsaan (national sermon) program, (2) the reinforcement of Ahlussunnah wal Jama'ah (Aswaja) ideology to foster a moderate and inclusive religious mindset, and (3) the preservation of Nusantara Islamic traditions as a culturally rooted approach. These efforts are reinforced by the leadership of the kiai (Islamic clerics), the continuity of religious traditions, and the availability of educational infrastructure. However, the pesantren faces several challenges, including limited human resources, the lack of integration between the de-radicalization efforts and the formal curriculum, and resistance from external actors. The study suggests that pesantren possess strategic potential as agents of culture-based de-radicalization. Therefore, it is recommended to enhance institutional capacity, improve the competencies of religious educators, and develop pesantren-based nationalism modules as part of broader national Islamic education policies.